Analysis of Pedagogical Aspects in the Study of the Problem of Bilingual in Teaching the Russian Language - Umarova Dilfuza Mamatkulovna (Periodica Journal, 2023)
The need to improve the methodology of bilingual education is due to the fact that the modern university has not yet properly organized systematic work with bilinguals, has not created an optimal methodology, it is still being created, with its help it will be possible to teach Russian to bilingual students. The practical goal of our study is formulated as follows: based on the experience of linguists, teachers, psychologists, linguomethodologists, to determine the most optimal methods of working with bilingual children for more successful mastering of the Russian language by students.
Keywords: bilingualism; degree; social function; language situation